Right hemicolectomy for primitive colon cancer - Colet, Andrés; Cassinasco, Angeles; Iacopino, Julio; Cilleruelo, Roberto; Praderi, José; Pastro, Dante; Pombo, Gabriel; Harretche, Martín; Estefan, Alberto; Praderi, Raúl (Cirugía del Uruguay, 1994)
operated on beca use of cander of the right colon between September 1987 and September 1989. They were 23 fema/es and 19 males between 39 and 88 years o/d with a media of 63 years. Classical centrípeta/ right hemicolectomy was performed in al/ cases. Peritoneum was not drained exceptin urgency. There was 2.3% operative mortality and 6.9% global mortality. There was one suture failure and 11 parietal suppurations. The authors point out the rise in the incidence of cancer of the colon and outline a study algorythm far patients at risk.